Child injury prevention: a survey of local authorities and health boards. Issue 4 (4th July 2017) - Chisholm, Anna; Watson, Michael C.; Jones, Sarah J.; Kendrick, Denise
Abstract: Aims: Unintentional home injuries are a significant global public health issue and are a major cause of mortality and morbidity. Within each country, injuries disproportionately affect children from low income families. Recent guidance issued in the UK recommends actions to be taken by local authorities to reduce injury rates and inequalities. This study aimed to describe and quantify child home injury prevention activities of local authorities (LAs) in England and health boards (HBs) in Wales. Methods: A questionnaire was sent to Directors of Public Health in all 153 upper-tier LAs in England and 7 HBs in Wales. The questionnaire covered the five broad areas recommended for injury prevention activities by NICE guidelines. Results: A response rate of 58% was achieved. NICE guidance (75%) and Public Health England guidance (57%) were most commonly used to support child injury prevention decision-making. Half (50%) of respondents had a child injury prevention alliance in their area. One fifth (19%) reported that their area had a written child injury prevention strategy. Fewer than half of responders provided training to practitioners about child unintentional injury prevention (43%), home safety assessments (43%) or an equipment scheme (43%). Of the 43% of areas with equipment schemes, most (59%) were small scale, supplying up to 200 families per year with equipment. Conclusions: Although some LAs/HBs show implementation of recent guidance on preventing home injuries in childhood, most do not. LAs/HBs are likely to need support to implement guidance in order that child injury rates and inequalities can be reduced.